Genetic Analysis of DEFECTIVE KERNEL1 Loop Function in Three-Dimensional Body Patterning in Physcomitrella patens . Issue 2 (2nd September 2014) - Demko, Viktor; Perroud, Pierre-François; Johansen, Wenche; Delwiche, Charles F.; Cooper, Endymion D.; Remme, Pål; Ako, Ako Eugene; Kugler, Karl G.; Mayer, Klaus F.X.; Quatrano, Ralph; Olsen, Odd-Arne
Abstract : A proposed regulatory loop segment of the DEK1 transmembrane domain is required for gametophore patterning in Physcomitrella patens . Abstract: DEFECTIVE KERNEL1 (DEK1) of higher plants plays an essential role in position-dependent signaling and consists of a large transmembrane domain (MEM) linked to a protease catalytic domain and a regulatory domain. Here, we show that the postulated sensory Loop of the MEM domain plays an important role in the developmental regulation of DEK1 activity in the moss Physcomitrella patens . Compared with P. patens lacking DEK1 ( ∆dek1 ), the dek1∆loop mutant correctly positions the division plane in the bud apical cell. In contrast with an early developmental arrest of ∆dek1 buds, dek1∆loop develops aberrant gametophores lacking expanded phyllids resulting from misregulation of mitotic activity. In contrast with the highly conserved sequence of the protease catalytic domain, the Loop is highly variable in land plants. Functionally, the sequence from Marchantia polymorpha fully complements the dek1∆loop phenotype, whereas sequences from maize ( Zea mays ) and Arabidopsis ( Arabidopsis thaliana ) give phenotypes with retarded growth and affected phyllid development. Bioinformatic analysis identifies MEM as a member of the Major Facilitator Superfamily, membrane transporters reacting to stimuli from the external environment. Transcriptome analysis comparing wild-type and ∆dek1 tissues identifies an effect on two groups of transcripts connected to dek1 mutant phenotypes: transcripts related to cell wall remodeling and regulation of the AINTEGUMENTA, PLETHORA, and BABY BOOM2 (APB2) and APB3 transcription factors known to regulate bud initiation. Finally, sequence data support the hypothesis that the advanced charophyte algae that evolved into ancestral land plants lost cytosolic calpains, retaining DEK1 as the sole calpain in the evolving land plant lineage.